165 PERFORMANCE FEEDBACK AND IMPROVEMENT IN PEDIATRIC RESIDENCY: A CONTROLLED TRIAL. (1st January 2005) - Wall, T. C.; Benton, E. C.; Willett, L. L.; Houston, T. K.
Abstract : Purpose: To assess the effectiveness of a physician performance feedback curriculum. Methods: We used standardized chart abstraction of patients seen in year 2003 in continuity clinic by PGY-1 and PGY-2 pediatric residents (N = 44) to assess performance. Intervention residents then received individual feedback compared to top performers in their resident peer group. In 2004, charts were re-abstracted. For comparison, we abstracted charts of 37 other historical control residents over 2 years prior to the study. Results: Age, gender, and race were similar among patients seen by intervention (N = 1105) vs. historical control (N = 1069) residents. Intervention residents had a greater change in the proportion of patients to whom they provided car safety and parental quit smoking advice (χ2; p < .01) (Table ). Using generalized estimating equations to adjust for clustering of patients within providers, patient characteristics, and number of visits, intervention residents were significantly more likely to advise about car seats (p = .013) and quitting smoking (p = .001). Conclusions: The intervention helped improve quality of care for some measures.